DEVELOPMENT AND STORAGE CHARACTERISTICS OF DEHYDRATED SALT MINCE FROM LOW PRICED FISH - NAIR, P RAVINDRANATHAN; GOPAKUMAR, K (Fishery Technology, 2017)
The study showed that less initial moisture with high salt content will be the best condition for enhanced storage life of dehydrated salt mince. Between sample I (10% salt per meat weight) and sample II (15% salt per meat weight) the latter was comparatively better in colour, odour and longer shelf-life. At room temperature the dehydrated salt mince has not showed any increase in total bacterial count. It is also found that the storage life of the salt mince can be enhanced to a significant extent by lowering the moisture content to below 10% and increasing the salt content to above 30%. Peroxide value, free fatty acid value, total volatile nitrogen and trimethylamine registered gradual increase during storage at room temperature forall the three samples. Among the three samples, the sample treated with 0.1% citric acid and 0.125% butylated hydroxy anisole was comparatively better in appearance and showed less rancidity as indicated by TBA values, upto a period of 15 weeks and thereafter all the three samples were almost similar in storage characteristics. Hence, the treatment with citric acid and B.H.A. has apparently not much significance in improving shelf-life and quality of salted dehydrated fish mince. Minced fish is the flesh separated in comminuted form from skin, bones, scales and fins from fish (Grantham, 1981). Yield of minced fish from a number of species ofIndian fish was worked by Perigreen (1981). According to him it varies from 29% (in shark) to 57% (in medium size soles). On an average, most of the species give an yield of about 45%. According to Perigreen & Jose (1983) minced threadfin bream has an accepted storage shelf-life at-23Â°C for 28 weeks beyond which the meat becomes inedible. Perigreen et al. (1979) have also calculated yield of minced fish from filleting waste. They have recovered about 6-10% minced meat from various species of fish. However, it should be noted that mincedfish has not captured a market in India. This paper deals with the studies on development of dehydrated salted fish mince andits shelf-life at ambient temperatures. Materials and MethodsJew fish (Johnius sp.) procured from Fort Cochin was brought to the laboratory in ice. Minced meat was prepared by using a hand separator after